The Hard Problem of Consciousness and the Free Energy Principle - Solms, Mark (Frontiers in Psychology, 2019)
This article applies the free energy principle to the hard problem of consciousness. After clarifying some philosophical issues concerning functionalism, it identifies the elemental form of consciousness as affect and locates its physiological mechanism (an extended form of homeostasis) in the upper brainstem. This mechanism is then formalised in terms of free energy minimisation (in unpredicted situations) where decreases and increases in expected uncertainty are felt as pleasure and unpleasure respectively. Emphasis is placed on the reasons why such existential imperatives feel like something to and for an organism.